2021
DOI: 10.1108/rjta-04-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of participants’ fit perceptions of customized garments

Abstract: Purpose The purpose of this study was to explore participants’ fit perceptions of customized garments and investigate the factors that affected the customized fit. Design/methodology/approach Because different patternmaking methods generate varied fit results, eight customized dresses were developed for four fit models aged 18–25 using two different made-to-measure (MTM) systems (Gerber AccuMark and Telestia Creator). The authors designed a questionnaire to assess the fit of the final garments on each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, diverse results were found regarding the effect of body characteristics, frequency of encountering fit problems and fit satisfaction on the fit preferences of the four RTW garments. BMI had no significant effect on the fit preferences of the respondents in four of the RTW garments which is consistent with Guo and Istook (2022) in lower-body garments but disagrees with Newcomb and Istook (2011) in upper garments. The size of garments the respondents wear affected fit preferences in T-shirts and jeans trousers, which is in agreement with Newcomb and Istook (2011) in casual tops.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, diverse results were found regarding the effect of body characteristics, frequency of encountering fit problems and fit satisfaction on the fit preferences of the four RTW garments. BMI had no significant effect on the fit preferences of the respondents in four of the RTW garments which is consistent with Guo and Istook (2022) in lower-body garments but disagrees with Newcomb and Istook (2011) in upper garments. The size of garments the respondents wear affected fit preferences in T-shirts and jeans trousers, which is in agreement with Newcomb and Istook (2011) in casual tops.…”
Section: Discussionsupporting
confidence: 52%
“…BMI was also found to be a significant predictor of men's polo shirt fit (Bizuneh et al, 2023). However, Guo and Istook (2022) found that BMI had no significant effect on the fit preference of women's dresses.…”
Section: Garment Fit Satisfactionmentioning
confidence: 86%
“…In their study, overweight men tended to frequently mention about the fit of their pants in the crotch, seat and hip areas, as well as the fit and sizing inconsistencies of their shirts (Stewart et al , 2014). Recently, Guo and Istook (2021) developed a 7-point scale of perceived fit preference from wearers (from −3: terrible to 3: excellent). Although the scale (Guo and Istook, 2021) was developed to evaluate dresses, it can be used to measure perceived fit preference for other types of clothing for men.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ashdown et al , 2006). Later, Guo and Istook (2021) used the scale of subjective fit preference developed in the study to objectively evaluate garment fit by experts in both live and photographed fit evaluation processes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation